Effect of Project Complexity on Elemental Cost Analysis Accuracy: A Case of Residential Construction Projects within Nairobi City County (International Journal of Scientific Research and Management (IJSRM), 2020)
The construction industry, in common with all industries, continually strives for progression and development. In view of the growing complexity in architectural designs, Quantity Surveyors have over years formulated and employed different cost estimating methods with a view to increase both accuracy and efficiency. However, very often these techniques are inaccurate and unstructured and are solely based on Quantity Surveyors’ own experiences and general purpose procedures. It remains unexplored in both international and Kenyan literature how the growing diversity in project complexity affects elemental cost analysis accuracy. Against this backdrop, the present study sought to determine the effect of project complexity on elemental cost analysis accuracy with reference to residential projects within Nairobi City County. The study used primary data which was quantitative in nature, collected by use of structured questionnaires. Both descriptive and inferential statistics were employed in data analysis. Findings reveal that site conditions are a significant determinant of elemental cost analysis accuracy among residential projects within Nairobi City County. The study also deduces that project size is a significant determinant of elemental cost analysis accuracy among residential projects within Nairobi City County. The level of technology used is also a significant determinant of elemental cost analysis accuracy among residential projects within Nairobi City County.